PENGARUH PDRB, PENGELUARAN PEMBANGUNAN DAN JUMLAH PENDUDUK PRODUKTIF TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN/KOTA DI SULAWESI TENGAH - Perwira, Ryan (Katalogis, 2018)
This study aims to determine the effect of GDP, development spending, and the total production population at PAD Regency / City in the province of Central Sulawesi. Data used in the study is secondary data in the form of time series data from 2013 to 2015. Variable independents consist of gross regional domestic product, development expenditure, and the number of productive population, while dependent variable of the study is local revenues. Data collected through observation, interviews, and documents, data is analyzed with multiple regressions analysis with partial and simultaneous tests. The finding show that gross regional domestic product, development expenditures, and the number of productive population simultaniously have positive and significant influence on local revenues. Development expenditure partially has significant influence on local revenues. Gross regional domestic product has dominant influence on local revenues in central sulawesi.